Internationalizing nursing curricula in a rapidly globalizing world - Wipada Kunaviktikul (2020)
© 2020 Rapid transformations in our globalizing world means there is an urgency for nurse educators to revitalize curricula to prepare nurses better for practice and the emphasis on achieving global health for all has never been greater. Nurses are being urged to collaborate across borders to achieve the United Nations' Sustainable Development Goals, through research, practice, policy and education. Thus, nurse educators and leaders need to consider the critical importance of internationalizing nurses’ education at all levels, as well being committed to their roles in curricula reform and using innovative technology. There are challenges to internationalization, but the benefits include helping nurses to grow cultural competence, developing strength in nursing voices globally, capacity building in global health, health policy and advocacy, growing scholarship in nursing across borders, developing the skills and knowledge of nurses from low-income countries, and forming partnerships to work together to achieve global health.